Pengaruh Literasi Keuangan, Gaya Hidup, dan Pendapatan terhadap Keputusan Berinvestasi Mahasiswa Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa Yogyakarta - Khoirul Fikri Hibatullah; Ratih Kusumawardhani; Pristin Prima Sari (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This research aims to analyze the influence of financial literacy, lifestyle, and income on the investment decisions of students of the Faculty of Economics of Sarjanawiyata University Tamansiswa Yogyakarta. The research uses a quantitative approach with a causality design. The research population is all active students of the Faculty of Economics in the 2024/2025 academic year, with a sample of 93 respondents determined using the Slovin formula and convenience sampling techniques. The data was collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression with classic assumption tests and hypothesis tests. The research results show that financial literacy, lifestyle, and income partially have a positive and significant effect on students' investment decisions. Financial literacy has the most dominant influence, followed by lifestyle and income. Simultaneously, these three variables have a significant effect on investment decisions with a determination coefficient value of 0.803, which means that 80.3% of the variation in investment decisions can be explained by the research model. This finding is in line with the Theory of Planned Behavior, which emphasizes the role of attitudes, subjective norms, and behavioral control in decision formation. This research emphasizes the importance of improving financial literacy, forming a rational lifestyle, and supporting the increase in student income to encourage early investment.